Implementation of the One-Stop Subdistrict Application (ASAKU) for Realizing Good Governance and Increasing Welfare Communities in Sidikalang Village - Manik, Fuzy Yustika; Hutagalung, Arif Qaedi; Saputra S, Kana (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Local government agencies at the sub-district level are also instructed to optimize the use of ICT in e-government development. Local government at the Kelurahan level is the basic foundation of public services and is the gateway for administrative processing up to the higher government levels. So local government at the sub-district level must continually improve satisfactory and good public services. This service is a community need that must be met. The still manual service system in sub-districts is the main problem that leads to community dissatisfaction and discomfort. So the innovation solution offered is to develop an integrated system (one-stop application). One application includes all the necessary systems and can be run online. The urgency of using information technology for the one-stop village application (ASAKU) at the Sidikalang village office, not only has implications for the field of communication but also influences every decision-making through automation and speed in data processing which ultimately affects services) District Office. The ASAKU application has several main features: e-government, e-archives, and e-commerce. These digital e-government services help improve government performance. With the implemented e-government, the Sidikalang sub-district wants to provide services without the intervention of public institution employees and support good governance. Through e-ASIP, all data and documents can be managed well, safely, and protected from loss. In addition, ASAKU is also a forum for the community to market agricultural products and products from MSMEs as well as products from social institutions such as youth organizations and PKK. Combining service providers (kelurahan) and the community with the proper adaptation of technology can create effectiveness and efficiency in managing areas at the kelurahan level. The main objective of the activity is the implementation and application of ASAKU so that local government institutions at the sub-district level can provide better (effective and efficient) public services by providing convenience for the community so that they can realize good governance. With this service activity, the Sidikalang sub-district can provide more optimal services. The public can submit letters in the Sidikalang sub-district using the ASAKU application which can be accessed anywhere and anytime. So that in the end it can realize good governance and improve the community's welfare in the Sidikalang sub-district.